Hepatic Angiomyolipoma: A Case Report and Literature Review - Ramzi Tababi MD; Mouna Medhioub MD; Ines Soussi MD; Imen Noomen MD; Yassine Kallel MD; Manel Yakoubi MD; Asma Ben Mohamed MD; Moufida Mahmoudi MD; Ghada Gharbi MD; Mahdi Bouassida MD; Emna Chelbi MD; Khaled Bouzaidi MD; et al. (Journal of Investigative Medicine High Impact Case Reports)
Hepatic angiomyolipoma (HAML) is an uncommon primary liver tumor with limited reported cases in the literature. It is composed of varying amounts of fat, smooth muscle, and blood vessels, typically non-malignant proliferation. It usually presents diagnostic challenges due to diverse imaging characteristics. We present a case of a 50-year-old female with a small HAML causing mild abdominal pain. It displayed radiographic characteristics mimicking hepatocellular carcinoma (HCC), and subsequent diagnosis was established upon histopathological findings of liver biopsy. The patient was radiologically monitored, and then she underwent surgical resection later on because of the size increase. Follow-up showed no signs of recurrence at 3 months. This case highlights the importance of histologic diagnosis of HAML if there are suggestive imaging features, given the variety of differential diagnoses. Symptoms or tumor growth is to be considered as warning signs that should lead to surgical resection, which remains the primary treatment modality.